A study on factors associated with malnutrition and risk of infections among malnourished children admitted to McGann teaching hospital, Shivamogga, Karnataka, India - Patil, Ravindra B.; Koppad, Raghavendraswamy Ramachandra; Benakanal, Shreeshail (International Journal of Research in Medical Sciences, 2017)
Background: Globally, each year malnutrition is implicated in about 40% of the 11 million deaths of under-five children in developing countries. Under nutrition is still the major problem in our country especially in underserved areas such as urban slums and rural areas. So we undertook this study to assess the factors associated with malnutrition and risk of infections among malnourished children. Methods: Study design: Analytical cross-sectional study. Duration: January 2013 - December 2013 (1 year). 182 malnourished children admitted to department of paediatrics during the study period. Prestructured-pre tested closed ended questionnaire was used to collect the data. The parents were interviewed; case sheets and other records were searched to get the necessary information. Results: The study was conducted among 182 under nourished children who admitted to department of paediatrics, in the calendar of 2013. Out of 182 children, 80 (43.96%) were boys and 102 (56.04%) were girls. More than 2/3rd (68.6%) under nourished children were in the age group of 0-3 years. Most common co-morbidity found was respiratory tract infection (44%) followed by acute gastro enteritis (22.5%) and fever (Pyrexia of unknown origine-22.5%). Conclusion: Children of relatively younger age, from rural areas and girls are the common victims of malnutrition. Respiratory tract infections and acute gastro-enteritis were the common co-morbid conditions found among malnourished children. Nutrition education has to be imparted to the people regarding consumption of cost effective nutritious diet (Emphasize it in Village health and Nutrition day).